The Phonological Awareness and Reading Ability among Early-Grade Learners - Ica Sulistianti; Hikmah; Ambo Dalle; Abdul Haris Sunubi; Mujahidah (Arabic and English Education Journal, 2025)
Background: Reading ability is a foundational literacy skill that plays a crucial role in children’s academic development. One of the key predictors of early reading success is phonological awareness, which refers to the ability to identify and manipulate sound structures in spoken language. Despite its significance, many early-grade learners still experience difficulties in decoding words due to low sensitivity to phonological components. Research Objectives: This study aims to examine the influence of phonological awareness on children’s reading ability and to identify which aspects of phonological awareness most strongly support word recognition and reading fluency at Ummusshabri School, Kolaka. Methods: This research employed a qualitative descriptive design involving early-grade students selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews with teachers, and document review of students’ reading assessments. The data were analyzed using thematic analysis to identify recurring patterns that reflect the relationship between phonological awareness skills and reading performance. Results: The findings show that students with stronger phonological awareness, particularly in phoneme segmentation, blending, and initial sound discrimination—demonstrated more accurate and fluent word reading. Students with limited phonological awareness exhibited difficulties in decoding, frequent mispronunciations, and slower reading rates. Teachers also reported that targeted phonological activities improved students’ reading progress over time. Conclusions: The study concludes that phonological awareness plays a substantial role in shaping early reading ability. Strengthening this skill through structured and engaging phonological instruction is essential for supporting students’ literacy development. Further research may explore intervention models to enhance phonological awareness in diverse classroom contexts.